INFLUENCE OF MILLIMETER RANGE ELECTROMAGNETIC WAVES ON HEMOLYSIS KINETICS OF RAT BLOOD ERYTHROCYTES (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The effect of millimeter range electromagnetic waves (MM EMW) on kinetics of acidic hemolysis of rat blood erythrocytes has been studied. It was shown that MM EMW affect the duration of erythrocyte hemolysis and this change depends on MM EMW exposure and frequency. At the irradiation by frequencies 41.8 and 42.2 GHz the acidic hemolysis occurs quicker at all durations of the irradiation compared to the control. At the irradiation by 50.3 and 51.8 GHz the hemolysis takes place quicker as well, as compared to the control at short durations of the irradiation. At the exposure 60 min the hemolysis start is delayed.
Keywords: millimeter range electromagnetic waves; irradiation; water resonant and non-resonant frequencies; hemolysis kinetics of erythrocytes